"Incentive hope" and the nature of impulsivity in low-socioeconomic-status individuals. (2019) - Walsh, Francesca; Cheries, Erik; Kwak, Youngbin
Abstract: Low-income environments have been associated with greater levels of impulsive behavior, which contribute to the higher debt and obesity rates that further perpetuate current wealth and health disparities. In this commentary, we describe how this might be explained by an appeal to "incentive hope" and the motivational drive toward consumption triggered by the future uncertainty these groups face.